2023
DOI: 10.3390/jpm13030471
|View full text |Cite
|
Sign up to set email alerts
|

The Progress and Pitfalls of Pharmacogenetics-Based Precision Medicine in Schizophrenia Spectrum Disorders: A Systematic Review and Meta-Analysis

Abstract: The inadequate efficacy and adverse effects of antipsychotics severely affect the recovery of patients with schizophrenia spectrum disorders (SSD). We report the evidence for associations between pharmacogenetic (PGx) variants and antipsychotics outcomes, including antipsychotic response, antipsychotic-induced weight/BMI gain, metabolic syndrome, antipsychotic-related prolactin levels, antipsychotic-induced tardive dyskinesia (TD), clozapine-induced agranulocytosis (CLA), and drug concentration level (pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Additionally, we examined their local genetic correlation and discovered they were correlated in 202 genomic regions, while only three of these remained signi cant after correction for multiple tests. The gene NFIL3 41 in the rst region (chr9: 94167203-96671698) and ve genes in the second region (chr11: 112459488-114257728) including NCAM1 42 , DRD2 43 , HTR3A 44 , HTR3B 44 , and ZBTB16 45 , were involved in the pathobiology of schizophrenia. While the relevant studies on frailty were relatively limited, we did not nd any risk genes that had been studied for frailty in these three regions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we examined their local genetic correlation and discovered they were correlated in 202 genomic regions, while only three of these remained signi cant after correction for multiple tests. The gene NFIL3 41 in the rst region (chr9: 94167203-96671698) and ve genes in the second region (chr11: 112459488-114257728) including NCAM1 42 , DRD2 43 , HTR3A 44 , HTR3B 44 , and ZBTB16 45 , were involved in the pathobiology of schizophrenia. While the relevant studies on frailty were relatively limited, we did not nd any risk genes that had been studied for frailty in these three regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings emphasize the need for a personalized approach toward treatment plans that consider the distinct pathophysiology of each symptom domain rather than overall symptom severity [ 8 , 9 ]. Moreover, our findings suggest that a hypothesis-free GWAS approach may advance the field [ 10 , 12 ]. This aligns with the recommendations of Siemens et al (2022), who conducted a systematic review of PGx PRS and found large discrepancies between those of candidate gene studies and GWAS, suggesting future studies should be hypothesis-free [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unweighted PRSs were created for candidate genes, CYP2D6, and CYP2C19, as no validated (i.e., effect sizes on antipsychotics outcomes) weights were available for the SNVs on the metabolizing enzymes. To construct the unweighted PRS with SNVs associated with antipsychotic response, candidate genes, which have been studied extensively over the past 10 years, were identified through a recent meta-analysis [ 12 ]. Only SNVs that showed significant results in an additive model in Caucasians were included in the PRS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations